Psycho Religious in Nursing Care on DM Type 2 Patients Towards Depression and Blood Sugar Reduction - Miadi Miadi; Kastudi Kastubi; Minarti Minarti; Noer Saudah; Chasiru Zainal Abidin (Humanistic Network for Science and Technology (HNST), 2019)
Effort to reduce depression and blood sugar levels through psycho religious of dzikir and shalawat was not carried out much yet. Research aims to explain psycho religious therapy effects towards depression and blood sugar level in Diabetes Mellitus type 2 patients (DM Type 2). This research used experimental method with randomized pre test post test control group design. This research was carried out on DM type 2 patients in Surabaya and they had been selected into two groups, given psycho religious group and control group. Blood sugar and depression measurement was carried out one week after and before psycho religious giving. Analysis data used Mann Whitney U test. While blood sugar concentration was analyzed using Paired t-test and Independent t-test. There was an effect of psycho religious towards depression of DM Type 2 patients, significant value of 0.004 (p